Arbitration clause in General Conditions of Business Transactions: current trends in international trade versus consumer arbitration - Vukadinović, Slobodan (Glasnik Advokatske komore Vojvodine, 2020)
This paper shows the diverging tendencies in the understanding of the arbitration clause contained in the general conditions of business transactions (GCBT) in (international) commercial and consumer law. The results show that the reverse logic is currently present regarding the issue of the arbitration clause contained in the GCBT and the necessity for such an arbitration agreement to be contained in a separate and signed document. International commercial arbitration, encompassing both legal dogmatic and arbitration and court practice, has shown a tendency towards a more liberal and flexible understanding of the written form in the past several decades, in terms of the validity of the arbitration clause contained in the GCBT referred to in the underlying substantive contract. By contrast, in consumer law, there is a tendency for the arbitration clause contained in the GCBT, which has not been brought to attention, to be considered a null and void provision. Namely, it is required for the arbitration clause to be contained in a separate document signed by both parties. This points to the conclusion that special attention should be paid to the consumer law disputes that are to be resolved by arbitration, while court and arbitration practice in international commercial disputes lately records cases in which the court explicitly took the opposite position. Trader’s claims stating that he was not aware that the GCBT contained arbitration clause and that no attention was drawn to it, are considered unfounded by the court. Namely, the application of both GCBT and arbitration in international trade are considered ordinary nowadays.